Electroencephalogram Detection for Insomnia Patients: A Preliminary Study - Inosensia Lionetta Pricillia; Ahmad Azhari (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Measurement of insomnia is currently generally carried out by medical practitioners by looking at the patient's condition accompanied by symptoms that refer to insomnia. In contrast, minimal quantitative measurements were found. This study proposes an alternative measurement with the acquisition of brainwave activity through electroencephalogram (EEG) in identifying sleep disorders. Insomnia is a common sleep disorder that can make it difficult to fall asleep difficult to stay asleep, or cause waking up too early and not being able to go back to sleep. Insomnia not only weakens energy levels and moods, but also a person's health, performance, and quality of life. This sleep disorder appears due to several factors, such as anxiety, stress, depression, bipolar disorder, or trauma. Photic stimulation is given as an attempt to find a person's body's response to light. Late adolescents with insomnia symptoms with an age range of 17-25 years were included as respondents, had previously been given a simulation test related to the treatment of sleep disorders, and identified severe, moderate, and mild insomnia. Acquisition using Narosky Mindwave Mobile 2 with the electrode in forehead position, Fp1. This study compares several types of insomnia data acquisition from previous studies and obtains patterns of insomniacs based on photic stimulation.